Hip-hop in Africa : prophets of the city and dustyfoot philosophers - Clark, Msia Kibona (Research in international studies. Global and comparative studies series ;, 2018)
Throughout Africa, artists use hip-hop both to describe their lives and to create shared spaces for uncensored social commentary, feminist challenges to patriarchy, and resistance against state institutions, while at the same time engaging with the global hip-hop community.